The Modern Afterlives of Old Irish Travel Narratives : From Gulliver to Star Trek - Petrovskaia, Natalia I. (Literary Reception & Art Reception, 2025)
This book explores the reception of the medieval Irish tradition of fantastic journey tales in Jonathan Swift's Gulliver's Travels , C.S. Lewis's The Voyage of the Dawn Treader , Umberto Eco's Baudolino , and the science fiction television franchises Star Trek and Stargate . In doing so, the book opens the door to a new history of literary reception, using Old Irish genre categories to analyse post-medieval texts. It aims to show that there is a family of texts produced in the post-medieval period that are heirs of the medieval Irish literary tradition of fantastic voyage narratives and that using Old Irish genre categories to analyse post-medieval works can open up new perspectives in our understanding of these works.